2019
DOI: 10.1093/braincomms/fcz045
|View full text |Cite|
|
Sign up to set email alerts
|

Two distinct prions in fatal familial insomnia and its sporadic form

Abstract: Fatal familial insomnia is a genetic prion disease, which is associated with the aspartic acid to asparagine substitution at codon 178 of the prion protein gene. Although the hallmark pathological feature is thalamic and olivary degeneration, there is a patient with an atypical fatal familial insomnia without the hallmark feature. The cause of the pathological variability is unclear. We analysed a Japanese fatal familial insomnia kindred and compared one atypical clinicopathological fatal familial insomnia phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…BvPrP with methionine at codon 109 of Prnp (22). Our work confirmed that also our model is susceptible to FFI.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…BvPrP with methionine at codon 109 of Prnp (22). Our work confirmed that also our model is susceptible to FFI.…”
Section: Discussionsupporting
confidence: 89%
“…This has been observed also in transgenic mice expressing BvPrP with isoleucine at codon 109 and the D178 mutation that spontaneously developed prion diseases with the presence of a PrP res with a predominant di-glycosylated band (34). Many other studies showed that this phenomenon occurred also in other transgenic mouse models inoculated with FFI thus suggesting that, regardless of the recipient mice, some biochemical features typical of the FFI are reproduced after inoculation (21,22).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations